Language-related episodes and pair dynamics in primary school CLIL learners: A comparison between proficiency-matched and student-selected pairs - Basterrechea, María; Gallardo-del-Puerto, Francisco (Studies in Second Language Learning and Teaching, 2020)
A considerable body of research within the interaction framework (Long, 1996) has centred on the language-related episodes (LREs) which occur when learners topicalize a specific linguistic item while they are engaged in meaning-focused tasks. Several studies have shown that the production of LREs may be influenced by the proficiency level of the learners (Kim & McDonough, 2008; Leeser, 2004). Sociocultural theory (Lantolf & Appel, 1994) has also explored collaborative work and the effect that pairing learners with the same proficiency levels or different patterns of interaction (Storch, 2002) has on the production of LREs (e.g., Mozaffari, 2017; Storch & Aldosari 2013), but little research has compared the effect of the pair formation method (student-selected vs. proficiency-matched) on young learners’ production of LREs and pair dynamics. This study compares young CLIL learners (aged 10-12) in student-selected and proficiency-matched pairs in task-based interaction. Results indicate that learners produce more meaning-based than form-based LREs, regardless of their pair formation method. The percentage of meaning-based LREs which are resolved accurately is much higher in proficiency-matched dyads than in student-selected ones. As for the patterns of interaction (Storch, 2002), the dynamics of proficiency-matched dyads are of a more collaborative nature than those of self-selected pairs.